2022
DOI: 10.1002/nop2.1199
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress, depression symptoms and fatigue among Quebec nursing staff during the COVID‐19 pandemic: A cross‐sectional study

Abstract: Aim: To describe the state of health of Quebec nursing staff during the pandemic according to their exposure to COVID-19, work-related characteristics and sociodemographic factors (gender, generational age group). State of health was captured essentially by assessing psychological distress, depression symptoms and fatigue. Design and methods:A large-scale cross-sectional study was conducted with 1,708 nurses and licenced practical nurses in Quebec (87% women, mean age of 41 ± 11 years). The survey included sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
(103 reference statements)
0
11
0
2
Order By: Relevance
“…The prevalence of anxiety and depression was higher than the percentages found in studies involving health professionals and nurses in Asia, which presented a range of 22%-37% for anxiety (Al Maqbali et al, 2021;Hao et al, 2021;Salari et al, 2020;Ślusarska et al, 2022) and 22%-35% for depression (Al Maqbali et al, 2021;Salari et al, 2020;Ślusarska et al, 2022). Peng et al (2022) identified that anxiety symptoms were directly linked to the development and maintenance of depression in nurses during the COVID-19 pandemic, which reinforced the thinking of nursing professionals about leaving their job or profession (Côté et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of anxiety and depression was higher than the percentages found in studies involving health professionals and nurses in Asia, which presented a range of 22%-37% for anxiety (Al Maqbali et al, 2021;Hao et al, 2021;Salari et al, 2020;Ślusarska et al, 2022) and 22%-35% for depression (Al Maqbali et al, 2021;Salari et al, 2020;Ślusarska et al, 2022). Peng et al (2022) identified that anxiety symptoms were directly linked to the development and maintenance of depression in nurses during the COVID-19 pandemic, which reinforced the thinking of nursing professionals about leaving their job or profession (Côté et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Notre cadre conceptuel s'appuie donc sur une approche du care, dans ses dimensions sociales, médicales, éthiques et politiques. Deux ans plus tard, les études qui s'intéressent à la souffrance morale chez ce dernier, particulièrement chez les infirmières, révèlent que les tensions que subissait le réseau de la santé étaient autant, sinon davantage, liées à des failles systémiques préexistantes dans le réseau de la santé québécois qu'à la virulence du SRAS-CoV 2 (Côté et al, 2022). C'est précisément le délabrement causé par ces failles qui a constitué le terreau fertile de la crise que nous traversons, dont les retentissements sanitaires proviennent de la convergence de crises écologiques, sociales et économiques amorcées depuis l'infiltration du modèle néolibéral jusque dans nos gouvernances (Brazil, 2022).…”
Section: Résuméunclassified
“…LTC nurses reported experiencing an overwhelming workload, high infection risk, job burnout, psychological distress, and fatigue during the COVID-19 pandemic (Fisher et al, 2021; Navarro Prados et al, 2022; White et al, 2021). A 2020 survey of Canadian nurses found that LTC nurses reported greater chronic, acute, and persistent fatigue compared to acute care nurses (Côté et al, 2022). The concerns of infection spreading to families and communities caused additional stress and escalated the fatigue (Lai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%